# Solve the following system using the substitution method. 3x – y = –2 6x + 5y = 24?

In the first equation, change it to y=3x+2 (move 3x to the right of the equal sign, and then divide by -1, since it is now -y). Equation #2 should now be 5y=-6x+24

Y=3x+2
5y=-6x+24

Substitute for x

5(3x+2)=-6x+24 eliminate parentheses with the distributive property
15x+10=-6x+24 combine like terms (x)
21x+10=24 eliminate constant (+,-)
21x=14 eliminate coefficient (*,/)
X=2/3 (: Plug it in to check for y
Y=4 I plug both answers into equation #2 to be sure. Hope this helps!
thanked the writer.
Mandy Clark commented
You're welcome(: Just a tip....if you're like me, I find the elimination method much easier than substitution. I solved this problem and got a fraction, so I solved it with elimination as well and got the same answer. It's never a bad thing to check. (:
3x - y = -2.....(1)
6x + 5y = 24...(2)
multiply by 5 in eq. (1) and add with eq. (2)
21x = 14
x = 14/21 = 2/3
put the value of x into eq. (1)
3*(2/3) - y = -2
2 - y = -2
y = 4
so, points are x = 2/3 and y = 4
thanked the writer. 